A synthesis of the literature to inform vaping cessation interventions for young adults. (August 2021) - Berg, Carla J.; Krishnan, Nandita; Graham, Amanda L.; Abroms, Lorien C.
Highlights: A major public health concern is e-cigarette use, particularly among young adults (YAs). YA e-cigarette ("vaping") cessation intervention research is limited. Research is needed to develop and optimize effective vaping cessation interventions. Vaping is a complex behavior, with particular implications for cigarette use. Promising delivery modes may be individualized and technology-based approaches. Abstract: There is an urgent need to address young adult (YA) vaping. However, there is limited vaping cessation intervention research, particularly studies tested via experimental designs. This manuscript focuses on YA vaping and critical needs for research to advance vaping cessation interventions for YAs. The smoking cessation literature, especially regarding YA smoking, provides evidence and theory from which to draw. However, the extent to which this literature has utility for vaping cessation warrants investigation. Research to inform the development and optimization of effective vaping cessation interventions for YAs requires attention to both potential targets for behavioral intervention (e.g., conceptual framework) and how to best reach YAs (i.e., delivery modality). Regarding the former, such interventions must consider the complexity of YA vaping (e.g., complex social influences, limited negative outcome expectancies, quit intentions). One particularly challenging aspect of YA cessation is co-use of other tobacco products and marijuana and ensuring that those who quit vaping do not continue or increase other product use. With regard to intervention modality, technology-based interventions (e.g., text messaging, apps) may prove promising, and individualized intervention (e.g., one-on-one counseling) may be needed to carefully intervene on the complexity of substance use, particularly cigarette and marijuana use, within this population.